Strength enhancement of concrete using incinerated agricultural waste as supplementary cement materials - Manan T.S.B.A.; Kamal N.L.M.; Beddu S.; Khan T.; Mohamad D.; Syamsir A.; Itam Z.; Jusoh H.; Basri N.A.N.; Mohtar W.H.M.W.; Isa M.H.; Shafiq N.; et al. (Nature Research, 2023)
The potassium (K) and sodium (Na) elements in banana are needed for hydration reaction that can enhance the strength properties of concrete. This research aims (a) to determine the material engineering properties of banana skin ash (BSA) and concrete containing BSA, (b) to measure the strength enhancement of concrete due to BSA, and (c) to identify optimal application of BSA as supplementary cement materials (SCM) in concrete. The BSA characterization were assessed through X-ray fluorescence (XRF) and Blaines air permeability. The workability, compressive strength, and microstructures of concrete containing BSA were analysed using slump test, universal testing machine (UTM) and scanning electron microscope (SEM). A total of 15 oxides and 19 non-oxides elements were identified in BSA with K (43.1%) the highest and Na was not detected. At 20g of mass, the BSA had a higher bulk density (198.43 0.00 cm3) than ordinary Portland cement (OPC) (36.32 0.00 cm3) indicating availability of large surface area for water absorption. The concrete workability was reduced with the presence of BSA (0% BSA: > 100mm, 1% BSA: 19 1.0mm, 2%: 15 0.0mm, 3% BSA: 10 0.0mm). The compressive strength increased with the number of curing days. The concrete microstructures were improved; interfacial transition zones (ITZ) decreased with an increase of BSA. The optimal percentage of BSA obtained was at 1.25%. The established model showed significant model terms (Sum of Squares = 260.60, F value = 69.84) with probability of 0.01% for the F-value to occur due to noise. The established model is useful for application in construction industries. 2021, The Author(s).